2008
DOI: 10.1021/jp0774847
|View full text |Cite
|
Sign up to set email alerts
|

Improved High-Temperature Stability and Sun-Light-Driven Photocatalytic Activity of Sulfur-Doped Anatase TiO2

Abstract: Of the various forms of titania (anatase, rutile and brookite) anatase is found to be the best photocatalyst. Without any chemical additives, the anatase to rutile transformation in pure synthetic titania usually occurs at a temperature range of 600 to 700 °C. High temperature (≥800 °C) stable photoactive anatase titania is required for antibacterial, application in building materials. A simple methodology to extend the anatase phase stability by modifying the titanium isopropoxide precursor by sulphur modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
138
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 227 publications
(144 citation statements)
references
References 58 publications
3
138
2
1
Order By: Relevance
“…It was also suggested that despite the decrease in band gap energy, metals were not always successfully introduced into the TiO 2 framework, and that the remaining metals on the outside surface sheltered the photoreaction sites [44]. Significant attention has been directed at reducing the band gap and in turn increasing the visible light activity of TiO 2 by doping with a range of non-metal elements including nitrogen [34,[45][46][47][48][49], carbon [43,[50][51][52][53], sulphur [54][55][56], phosphorous [57], boron [58,59], oxygen [60], and fluorine [61,62], along with heterojunctions [63][64][65][66][67] and combinations of these elements [68][69][70][71][72][73].…”
Section: Introductionmentioning
confidence: 99%
“…It was also suggested that despite the decrease in band gap energy, metals were not always successfully introduced into the TiO 2 framework, and that the remaining metals on the outside surface sheltered the photoreaction sites [44]. Significant attention has been directed at reducing the band gap and in turn increasing the visible light activity of TiO 2 by doping with a range of non-metal elements including nitrogen [34,[45][46][47][48][49], carbon [43,[50][51][52][53], sulphur [54][55][56], phosphorous [57], boron [58,59], oxygen [60], and fluorine [61,62], along with heterojunctions [63][64][65][66][67] and combinations of these elements [68][69][70][71][72][73].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this is its applications in several industries, most notably in the production of ceramic materials (e.g. wall tiles) which retain an antibacterial property [39]. Additional areas which have been identified as benefitting from a high temperature stable form of anatase are sanitary wares and self-cleaning glass.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3,4,5,6 Of the semiconducting materials, ZnO offers significant opportunity in providing electronic, photonic, and spin-based functionality (spintronics) because of its direct wide band gap (3.37 ev) and large exciton binding energy of ~60 meV. This makes it worthy in the potential and established hi-tech applications such as ceramics, piezoelectric transducers, optical coatings, high speed and display devices, 7,8,9,10 gas sensors, 11 varistors, 12, 13 photocatalysts 14 and photovoltaics.…”
Section: Introductionmentioning
confidence: 99%